What Should We Expect from Somebody Who Teaches Mathematics in Elementary Schools? - Vinner, Shlomo (Scientia in educatione, 2013)
This paper is an extension of my plenary talk in SEMT 11 (Vinner, 2011) in which I promised to elaborate on some issues that I could not discuss at the talk because of time restrictions. The paper recommends that, in addition to the mathematical knowledge needed for teaching in elementary schools, attention should be given to other aspects of the teacher’s work. It is suggested that the rationale of teaching mathematics as a compulsory subject to the entire population should be discussed with the teachers as well as the ultimate goals of education. The paper recommends also avoiding in teacher training topics which are beyond the zone of proximal development (ZPD) of the teachers.